Chemical engineering of the peptidyl transferase center reveals an important role of the 2′-hydroxyl group of A2451 - Erlacher, Matthias D. (Oxford University Press, 2005)
The main enzymatic reaction of the large ribosomal subunit is peptide bond formation. Ribosome crystallography showed that A2451 of 23S rRNA makes the closest approach to the attacking amino group of aminoacyl-tRNA. Mutations of A2451 had relatively small effects on transpeptidation and failed to unequivocally identify the crucial functional group(s). Here, we employed an in vitro reconstitution system for chemical engineering the peptidyl transferase center by introducing non-natural nucleosides at position A2451. This allowed us to investigate the peptidyl transfer reaction performed by a ribosome that contained a modified nucleoside at the active site. The main finding is that ribosomes carrying a 2′-deoxyribose at A2451 showed a compromised peptidyl transferase activity. In variance, adenine base modifications and even the removal of the entire nucleobase at A2451 had only little impact on peptide bond formation, as long as the 2′-hydroxyl was present. This implicates a functional or structural role of the 2′-hydroxyl group at A2451 for transpeptidation.